Microwave detection of defects and inhomogeneities in low pressure injection moulded β-TCP ceramic - Martins, S.T.; Hädrich, Helmut; Dannheim, Henning; Weinzierl, Jochen; Greil, Peter; Dannheim, Henning (Advanced Engineering Materials, 2004)
The feasibility of a nondestructive microwave inspection to detect internal processing defects in low pressure injection moulded ceramic parts was investigated. A β-TCP (β-tricalcium phosphate, Ca(PO )) slurry with paraffin, ethylene vinyl acetate copolymer and stearic acid as binder system was injection moulded with a pressure of 0.2 MPa and subsequently inspected in a 94.1 GHz microwave testing device. The transmitting amplitude and phase displacement images were compared with visual inspection of the samples. The novel method was able to detect, localize and geometrically characterize inhomogeneities and non-visible defects present in green ceramic compacts.